2018
DOI: 10.1029/2018jc013958
|View full text |Cite
|
Sign up to set email alerts
|

Can Rogue Waves Be Predicted Using Characteristic Wave Parameters?

Abstract: Rogue waves are ocean surface waves larger than the surrounding sea that can pose a danger to ships and offshore structures. They are often deemed unpredictable without complex measurement of the wavefield and computationally intensive calculation, which is infeasible in most applications; consequently, there a need for fast predictors. Here we collate, quality control, and analyze the largest data set of single‐point field measurements from surface following wave buoys to search for predictors of rogue wave o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 63 publications
3
42
1
Order By: Relevance
“…It is difficult to know H max with precision because although the population of waves approximates a Rayleigh distribution, the upper tail does not conform (e.g., Krogstad, 1985), and the H max /H s ratio varies with the number of waves considered (Michel, 1999). Generally, however, when computed on intervals of 20 min to an hour (the common integration time for buoy data), H max is approximately 2 H s (Krogstad, 1985;Cattrell et al, 2018;Oliveira et al, 2018).…”
Section: Data Availability Statementmentioning
confidence: 99%
“…It is difficult to know H max with precision because although the population of waves approximates a Rayleigh distribution, the upper tail does not conform (e.g., Krogstad, 1985), and the H max /H s ratio varies with the number of waves considered (Michel, 1999). Generally, however, when computed on intervals of 20 min to an hour (the common integration time for buoy data), H max is approximately 2 H s (Krogstad, 1985;Cattrell et al, 2018;Oliveira et al, 2018).…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Since the late 1990s, there has been an increasing number of studies analyzing observed rogue waves or studying potential mechanisms for rogue wave generation. Such studies comprise the description and analysis of measurements of individual rogue wave events (e.g., Skourup et al, 1997;Haver, 2004;Magnusson and Donelan, 2013) or the description of rogue wave statistics from longer records (e.g., Chien et al, 2002;Mori et al, 2002;Stansell, 2004;Baschek and Imai, 2011;Christou and Ewans, 2014). Several studies contain attempts to identify potential physical mechanisms of rogue wave formation, such as second-order nonlinearities (Fedele et al, 2016), modulational instability (Benjamin, 1967) caused by nonlinear wave focusing (Janssen, 2003), or the directionality of the wave spectrum (Onorato et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, for an operational wave model, defining C 4 using Equation (12), a six dimensional integral, is too computationally expensive (Cattrell et al 2018). Rogue waves most likely occur when the spectrum is narrow banded.…”
Section: Wammentioning
confidence: 99%
“…significant wave height, wave periods and directions). These are determined by response amplitude operators (RAO; Cattrell et al 2018). Unfortunately, the RAOs are not available for the SS El Faro hence this manuscript focusses on the environmental conditions that the vessel experienced.…”
Section: Introductionmentioning
confidence: 99%